Religious rationalism of Wiszowaty and Leibniz - Kosiński, Paweł (Hybris, 2015)
The purpose of this article is to show that religious rationalism presented by Polish Socinian Andrzej Wiszowaty is different from Leibniz’s religious rationalism. At the beginning of the article the author analyzed the dispute between Wiszowaty and Leibniz about Trinity. While comparing religious and philosophical concept of Wiszowaty and Leibniz the author has proved that both philosophers presented different views related to the nature of God, perception of the truths of faith, predestination and miracles. Wiszowaty in a dispute about the Trinity represented Socinian ideas and believed the dogma of the Trinity is contrary to the reason and inconsistent with the Bible, while Leibniz defended the Christian dogma against the alleged contradictions.